Morphological and Phytochemical Studies on Xanthium strumarium L. - Chavan, S T; Kulkarni, A U (Plantae Scientia, 2021)
Xanthium strumarium L. belonging to family Asteraceae is an annual herb with abundance occurring in India. This plant has been used in the indigenous system of medicine for a long time in India as well as other countries. The morphological studies reveal that there is notable difference in the plant habit, leaves, stem, root and flowers among this plant. Morphological study also helps for correct identification and nomenclature of plant. The chemicals present in root, stem and leaves drugs are analyzed physically as well as chemically by qualitative and quantitative parameters. In present study reveals morphology, medicinal properties and phytochemical studies of plants for correct identification authenticity of drugs. The details are presented in the present paper.